Representation Of Legal Assistance Against The Criminal Action Of Murder In Tulehu In The State Court Of Ambon, Indonesia - Fauziah Rahawarin (LEGAL BRIEF, 2022)
This study aims to represent legal assistance to the accused of the crime of murder in Tulehu which was tried at the Ambon District Court. This type of research is a qualitative research. There are two types of research data, namely primary data and secondary data. Primary data is the main data in the form of interviews with informants, while secondary data is documentation data that supports the research results. This research technique includes three stages, namely, the process of (1) reduction, (2) presentation, and (3) drawing conclusions. The results of this study concluded that 2. The protection of the rights of the accused of the crime of murder in Tulehu is not in accordance with the rule of law. The service for granting the rights of the accused through legal assistance provided to the accused of the crime of murder in Tulehu is not in accordance with the rule of law, this is because law enforcers in the sense of prosecutors and judges have not optimally carried out trial procedures according to the directions or instructions in the Criminal Procedure Code and the law. the law in order to create justice in maintaining the rights of the defendant. The prosecutor did not provide complete proof of the guilt of the defendant in the Tulehu murder crime in the facts of the trial, thus affecting the rights of the accused in order to obtain legal certainty and a sense of justice